(untitled) (Horizontes de Enfermería, 2023)
There is a window of opportunity in development during the 1000 days of a person’s life, where inequalities and gaps can be reduced. This research had the objective of analyzing the evolution and determinants of chronic childhood malnutrition in Carchi during the first 1000 days of life. The study methodology was quantitative through econometric regression and a data pooling model. The main result of the study is complicated since childhood chronic malnutrition in children under 1000 days of age has increased in the province, with multidimensional determinants.